Strategi Self-Regulated Learning untuk Menurunkan Tingkat Prokrastinasi Akademik Siswa - Muhammad Iqbalul Ulum (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2016)
Academic procrastination is a behavior that should be avoided by students because it would give a bad influence, especially the academic achievement. One of the factors that lead to academic procrastination is lack of self-regulation in learning. Therefore, it is necessary for students to have self-regulated learning. This research aimed to test the self-regulated learning strategy to reduce the level of academic procrastination XI grade student of SMAN 1 Ngamprah of the academic year 2015/2016 West Bandung Regency. The method used is a quasi-experimental nonequivalent (pretest and posttest) control group design. Sampling was done by using purposive sampling technique. Instrument used is The Academic Procrastination State Inventory (APSI) developed by Henri C. Schouwenburg. The sample are 68 students whereas devided into experiment and control group. Data analyzed using the Mann-Whitney test. Result shows that self-regulated learning are effective for lowering the level of academic procrastination.